Enhanced activity of selenocyanate-containing transition metal chalcogenides supported by nitrogen-doped carbon materials for the oxygen reduction reaction. Issue 13 (7th June 2019) - Jhong, Huan-Ping; Chang, Sun-Tang; Huang, Hsin-Chih; Wang, Kai-Chin; Lee, Jyh-Fu; Yasuzawa, Mikito; Wang, Chen-Hao
Abstract : The SeCN − containing transition metal chalcogenides supported by nitrogen-doped carbon catalyzes the ORR activity. Abstract : Selenocyanate-containing transition metal chalcogenides supported by nitrogen-doped carbon materials, denoted as CoSe/CN, demonstrate an excellent oxygen reduction reaction (ORR) ability with an electron-transfer number of 3.994, which is approximately equal to the ideal electron-transfer number 4.0. In an electrochemical measurement, CoSe/CN demonstrates excellent durability after 30 000 cycles. When an anion (alkaline) exchange membrane fuel cell uses CoSe/CN as the cathode catalyst, it shows high performance using a Fumapem FAA-3 membrane. The high catalytic performance of CoSe/CN is due to two reasons: 1) the presence of selenocyanate (SeCN − ) bonding in CoSe/CN that promotes electron transfer and 2) the presence of the Co–N structure that acts as the active site for the ORR. These characteristics of CoSe/CN enhance the performance of the active sites and increase the kinetic reaction rate during the ORR, thus making CoSe/CN a promising catalyst.